Stylistics In Tafsir Al-Fakhr Al-Razi And And Its Impact On The Development Of Arabic Rhetoric/ الأسلوبيّة في تفسير الفخر الرّازيّ وأثرها في تطوّر البلاغة العربيّة - Al-Lahham, Reem Rateb Al-Sayed; Mohieldin, Hazem (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
In the modern era, a science called contemporary stylistics appeared, which reached to describing texts and searching for what distinguishes them and the authors’ unique way of arranging them. And this science has its roots in our Arabic rhetorical heritage. Ancient rhetoricians such as Al-Fakhr Al-Razi preceded them with these stylistic studies. Therefore, this research sought, using the analytical descriptive method, to study the proof of the existence of such stylistic studies in Al-Fakhr Al-Razi through his Tafsir of Surat Al-Roum, revealing his great interest in explaining the types of Qur'anic styles, and their levels (morphological - synthetic - semantic), most of which were from Al-Razi's efforts. No one preceded it, but everyone who came after him benefited from it, Especially in semantics and correspondences between verses and surahs.